Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1194/jlr.m200067-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

In vivo investigation of the placental transfer of 13C-labeled fatty acids in humans

Abstract: Placental fatty acid transfer in humans in vivo was studied using stable isotopes. Four pregnant women undergoing cesarean section received 4 h before delivery an oral dose of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 29 publications
(34 reference statements)
7
58
0
Order By: Relevance
“…Laws, Laws, Lean, Dodds and Clarke transported across the placenta more readily than those found in the other oils studied, although this theory is unlikely as it contradicts data from studies in rats and humans (Haggarty et al, 1997;Amusquivar and Herrera, 2003;Larque et al, 2003;Ortega and Herrera, unpublished data). Recent research has suggested that the type of dietary fat rather than the total fat content of the diet is important in determining neonatal outcome (Jean and Chiang, 1999;Rooke et al, 2001a, b and c).…”
Section: --mentioning
confidence: 79%
“…Laws, Laws, Lean, Dodds and Clarke transported across the placenta more readily than those found in the other oils studied, although this theory is unlikely as it contradicts data from studies in rats and humans (Haggarty et al, 1997;Amusquivar and Herrera, 2003;Larque et al, 2003;Ortega and Herrera, unpublished data). Recent research has suggested that the type of dietary fat rather than the total fat content of the diet is important in determining neonatal outcome (Jean and Chiang, 1999;Rooke et al, 2001a, b and c).…”
Section: --mentioning
confidence: 79%
“…However, there is evidence that this order of selectivity is not fixed, but that it can change with the particular mixture of fatty acids available in the maternal circulation (Haggarty et al, 1999), which in turn is largely determined by the maternal diet. Recent in vivo evidence from sophisticated tracer studies using 13 C-labelled fatty acids administered to the mother immediately before caesarean section have also shown selective channelling of particular fatty acids to the fetal circulation (Larque et al, 2003).…”
Section: Maternalmentioning
confidence: 99%
“…In addition, recent data indicate that there is inter-individual variation in the ability to convert the precursor ALA to n-3 LCPUFA and, particularly to DHA, which is related to common polymorphisms in the human ∆-5 and ∆-6 desaturase genes FADS1 and FADS2 (Schaeffer et al, 2006). DHA is preferentially transferred across the human placenta to the foetus mediated by specific transfer proteins (Larque et al, 2003 and.…”
Section: Cis N-3 Polyunsaturated Fatty Acids (N-3 Pufa)mentioning
confidence: 99%